Recent Advances in Catalysis Based on Transition Metals Supported on Zeolites - Sánchez-López, Perla; Kotolevich, Yulia; Yocupicio-Gaxiola, Rosario I.; Antúnez-García, Joel; Chowdari, Ramesh Kumar; Petranovskii, Vitalii; Fuentes-Moyado, Sergio (Frontiers in Chemistry, 2021)
This article reviews the current state and development of catalytic processes using transition metals (TM) supported on zeolites (TM/Z), as well as the contribution of theoretical studies to understand the details of the catalytic processes. Structural features inherent to zeolites, and their corresponding properties such as ion exchange capacity, stable and very regular microporosity, the ability to create additional mesoporosity, as well as the potential chemical modification of their properties by isomorphic substitution of tetrahedral atoms in the crystal framework, make them unique catalyst carriers. New methods that modify zeolites, including sequential ion exchange, multiple isomorphic substitution, and the creation of hierarchically porous structures both during synthesis and in subsequent stages of post-synthetic processing, continue to be discovered. TM/Z catalysts can be applied to new processes such as CO2 capture/conversion, methane activation/conversion, selective catalytic NOx reduction (SCR-deNOx), catalytic depolymerization, biomass conversion and H2 production/storage.